2016
DOI: 10.18632/oncotarget.11563
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin potentiates antitumor activity of cisplatin in bladder cancer cell lines via ROS-mediated activation of ERK1/2

Abstract: Resistance of bladder cancer to cisplatin is a major obstacle to successful treatment. In the current study, we investigated the apoptotic effects of curcumin and cisplatin co-treatment in 253J-Bv(p53 wild-type) and T24(p53 mutant) bladder cancer. We found that curcumin and cisplatin co-treatment primarily targets reactive oxygen species(ROS) and extracellular regulated kinase(ERK) signaling during the apoptosis induction in bladder cancer. The apoptosis rate in 253J-Bv and T24 cells co-treated with curcumin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
70
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 34 publications
3
70
1
1
Order By: Relevance
“…In light of our previous findings regarding the role of AEs as prooxidant players on breast cancer cells [27], this study has explored the ability of AEs to sensitize breast cancer cell to conventional chemotherapy through oxidative process. Based on literature data [38][39][40][41][42], our results strongly support the prooxidant role of AEs/PTX in hindering breast cancer cellular growth associated with ROS production. To further confirm the important role of ROS in enhancing the antitumor effect of the combined treatment, we demonstrate that the well-known antioxidant NAC attenuates the synergistic and antitumor effect on MDA-MB231 cells.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In light of our previous findings regarding the role of AEs as prooxidant players on breast cancer cells [27], this study has explored the ability of AEs to sensitize breast cancer cell to conventional chemotherapy through oxidative process. Based on literature data [38][39][40][41][42], our results strongly support the prooxidant role of AEs/PTX in hindering breast cancer cellular growth associated with ROS production. To further confirm the important role of ROS in enhancing the antitumor effect of the combined treatment, we demonstrate that the well-known antioxidant NAC attenuates the synergistic and antitumor effect on MDA-MB231 cells.…”
Section: Discussionsupporting
confidence: 82%
“…ROS cellular levels are thus crucial for designing advanced therapies and a future challenge in anticancer treatment [58]. There are many reports describing the prooxidant effect of polyphenols in sensitizing cancer cells to chemotherapeutic drugs through different pathways [38][39][40][41][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated that ERK activation induces apoptosis under specific conditions, such as excessive ROS generation or oxidant scavenging failure ( 25 ). According to Zuo et al ( 26 ), alternol, an antitumor agent used in the treatment of osteosarcoma, increases ROS levels by activating ERK and subsequently inhibiting STAT3 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%